A comprehensive threat analysis to support the red list of marine and coastal ecosystems of Colombia - Uribe, Edwin S.; Etter, Andrés; Luna-Acosta, Andrea; Diazgranados, María Claudia; Alonso, David; Chasqui, Luis; Osorno, Adriana; Acosta, Alberto; Rodríguez-Rodríguez, Alexandra; Ricaurte-Villota, Constanza; Escobar, Luisa; Giraldo, Alan (Frontiers in Marine Science, 2022)
IntroductionHuman activities represent a growing threat to biodiversity, increasing species extinction and leading ecosystems to collapse. The knowledge of the spatial distribution of threats to ecosystems is fundamental to understanding their risk of collapse as defined by the Red List of Ecosystems, an International Union for Conservation of Nature (IUCN) global standard to guide conservation and management actions. Colombia is a megadiverse country; almost half of its territory is marine, and its ecosystems are subject to anthropogenic and climatic threats.MethodologyThis study provides a quantitative map assessment for a set of relevant anthropic and climatic threats and impacts on the marine and coastal areas of Colombia, intending to perform the threat description component of the Red List assessment protocol. A cumulative impact assessment was applied to analyze the threat levels (TLs) and impact levels of 12 anthropogenic and climatic pressures.ResultsThe observed TL patterns meet spatial expectations, revealing that the assessment units in the Caribbean Sea are more threatened than those in the Pacific Ocean, and continental areas are more threatened than the oceanic ones. Habitat transformation and sea warming were the threats with the most impact on coastal and marine ecosystems, respectively. Climatic threats were widely extended throughout the study area, occurring even in the most pristine zones (e.g., Malpelo Island).DiscussionClimate threats are challenging to national conservation strategies since these pressures are not completely manageable at local scales as they depend mainly on global efforts. Recommendations drawn from this work can guide actions for the conservation of the ecosystems of Colombia.